Bahasa Gender dalam Novel Perempuan di Titik Nol Karya Nawal El-Saadawi - Siva Atali Aulia; Yunita Suryani; Salimulloh Tegar Sanubarianto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
The novel Women at Point Zero by Nawal El Saadawi discusses gender language which is linked to Robin Lakoff's theory regarding language and gender. Discussions related to language and gender are interesting to research because there are still many patriarchal cultures and gender injustices that exist in certain areas, as is the case in this novel about Women At Point Zero. The aim of this research is to find out what gender language is contained in the novel as knowledge for readers and also for future learning. The method used in this research is a qualitative descriptive method. The techniques used are documentary and thematic analysis techniques. Of the several gender languages contained in the novel, the word